Patient safety culture through the lenses of surgical patients: a qualitative study - Magnhild Vikan; Arvid S. Haugen; Berit T. Valeberg; Ann K. Bjørnnes; Vigdis K. S. Husby; Ellen CT. Deilkås; Stein O. Danielsen (BMC Health Services Research)
Abstract Background Patient engagement and learning from patients’ experiences may increase patient safety and reduce the occurrence of adverse events. Most adverse events are related to surgery, and patient outcomes are positively associated with patient safety culture. This study aimed to explore former surgical patients’ perspectives and experiences of adverse events and patient safety culture during their surgical pathway and identify themes relevant to adverse event causes and quality improvement projects. Methods The design of this qualitative study was explorative, utilizing an abductive approach. We purposefully recruited former surgical patients from Norwegian user organizations based on group characteristics sampling. The participants were 57% men and 43% women, aged 35 to 64 years. We conducted 14 individual semi-structured interviews between 18/01/24 and 07/03/24 using Zoom’s video audio software, with an average duration of 65 min. We analyzed the data using Braun and Clarke’s method for reflexive thematic analysis, and generated themes by examining patterns of meaning throughout the dataset. Results Data analysis generated three themes concerning the former surgical patients’ perspectives of patient safety culture and adverse events: (1) “Personalized care and predictable pathways increase patients’ sense of safety”; (2) “Surgical patients’ involvement: Aspire to be a resource – Not a threat”; and (3) “Time to cultivate a culture that fosters improvements and reconciliation.” Conclusions This study provided insight into patients’ perspectives on adverse events and patient safety culture in the surgical context. The patients underscored the value of predictable plans in caregiving, tailored information, personalized care, and dialogue on equal terms. They considered the demand for efficiency, professional hierarchy, status, prestige, and authority to be barriers to patient engagement and safety. Interventions to improve a culture of openness, psychological safety, and organizational learning in the surgical context could increase the safety of patients and healthcare professionals. Finally, acknowledgment of adverse events, information, and follow-up were essential for patients and next of kin to move on after an adverse event.